A comparative study of governance of professional baseball systems in Japan and Taiwan - Lee, P.-C.; Takahashi, Y.; Lin, C.-Y.; Sasaki, K. (The Sport Journal, 2010)
This paper has provided a basis to outline some key governance features of professional baseball systems both in Japan and Taiwan. It seeks to highlight and compare with the various forms of interactions between actors in these two systems. Associated with this, the paper undertakes a qualitative content analysis method with reviewing and explaining the dynamics in the interactions among three main actors, namely, state, owners of clubs, and players. Four principal conclusions are as follows: first, this case points to evidence that owners of clubs own dominant power while players` voices are relatively weak; second, it demonstrates how these two states adopt different attitudes to intervene or non-intervene their domestic professional baseball industry in some respects; third, it identifies the most powerful actors in the two systems are Committee Mediation and Committee Board, which represent the extended power of clubs` owners; finally, the article suggests that the outcomes of interactions between the above actors have shaped the two sporting contexts for managerial decisions, which have made a contribution to a development of their own operating mechanisms.